The Dilemmas of Water Quality and Food Security Interactions in Low- and Middle-Income Countries - Linderhof, Vincent; de Lange, Thijs; Reinhard, Stijn (Frontiers in Water, 2021)
Water is a factor input for many food system activities such as agriculture, food processing and consumption. However, food system activities also affect water resources. Moreover, the shift in focus of food security in Low- and Middle-Income Countries (LIMCs) from producing enough staple foods towards healthy diets stimulates local production of fresh food such as fruit, vegetables and fish even in water scarce regions. To secure local production, polluted water is used for food production, processing and consumption, which might jeopardize human health. However, scientific evidence is still scattered and fragmented. The aim of this study is to systematically investigate the role of water quality on the food system and vice versa. Using a comprehensive framework, we sketch the inter-relationships between water quality and food systems based on a literature study. Food system activities included were food production (crop production, livestock and aquaculture), food processing, and food consumption. Multiple contaminants were incorporated such as nitrogen, phosphorus, pesticides, pathogens, cyanotoxins, and heavy metals. Moreover, we considered different water sources such as groundwater, surface water, wastewater and coastal water. We found that food system activities contaminate water in several ways, and these differ between food system activity and type of food produced. The impact of water quality on the food system depends on the food produced, the type of contaminant and techniques of food preparation. In addition, food is contaminated in multiple ways along the food system. Irrigation with polluted water may sound familiar, but polluted water is sometimes also used in food processing (cleaning of equipment or food products), and in food preparation (at home or by street vendors). Hygiene in food consumption is crucial to prevent fecal-oral transmission. However, water, sanitation and hygiene (WASH) received little attention in relation to food consumption. If local production of fresh food is encouraged to improve food security, all aspects of water quality should be analyzed to avoid undesirable consequences.